Bahan Ajar, Android - M. Nizomul Asfari; Muhammad Fahrurrozi (Badan Penelitian dan Pengabdian Masyarakat (BP2M) STMIK Syaikh Zainuddin NW Anjani, 2023)
At this time Smartphones are not only owned by the upper class, but almost all groups. Because smartphones have many benefits, including as a learning medium for school children. The purpose of this research is to make a Microsoft Office teaching material application with the Android operating system. This application was created using Android Studio with the Java programming language. In this study the system design method used is the waterfall method. The results of this study are an android program in the form of Microsoft Office learning materials that will be used for students of Madrasah Tsanawiyah Nahdlatul Wathan Kalijaga Timur. Testing this application is reviewed based on several criteria, namely from the appearance of the application, the contents of the application material, and the benefits of the application to users.